2016
DOI: 10.1017/s1751731115002906
|View full text |Cite
|
Sign up to set email alerts
|

Multi-generational imputation of single nucleotide polymorphism marker genotypes and accuracy of genomic selection

Abstract: Availability of high-density single nucleotide polymorphism (SNP) genotyping platforms provided unprecedented opportunities to enhance breeding programmes in livestock, poultry and plant species, and to better understand the genetic basis of complex traits. Using this genomic information, genomic breeding values (GEBVs), which are more accurate than conventional breeding values. The superiority of genomic selection is possible only when high-density SNP panels are used to track genes and QTLs affecting the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In GSs_Icd_pop, the annual genetic gain remained higher (+ 9.5%) than in the classical design but was substantially lower than in GSs_Icd (+ 45%). The contribution to the analysis of co-segregation between VLD and MD SNPs has already been reported in previous studies which highlight the beneficial effect of including relatives in the reference population for imputation [ 21 , 24 , 26 , 27 , 29 31 , 34 ], especially sires and grandsires [ 24 ]. The effect of including close relatives in the reference population on genomic prediction accuracy was also pointed out by previous studies on simulated and real data [ 38 , 56 ].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In GSs_Icd_pop, the annual genetic gain remained higher (+ 9.5%) than in the classical design but was substantially lower than in GSs_Icd (+ 45%). The contribution to the analysis of co-segregation between VLD and MD SNPs has already been reported in previous studies which highlight the beneficial effect of including relatives in the reference population for imputation [ 21 , 24 , 26 , 27 , 29 31 , 34 ], especially sires and grandsires [ 24 ]. The effect of including close relatives in the reference population on genomic prediction accuracy was also pointed out by previous studies on simulated and real data [ 38 , 56 ].…”
Section: Discussionmentioning
confidence: 94%
“…Population-based methods use the linkage disequilibrium (LD) between SNPs and haplotype frequencies only, whereas population- and family-based methods also include co-segregation information based on pedigree. The factors that affect imputation accuracy [ 21 35 ] and the relation between imputation accuracy and genomic prediction quality [ 21 , 25 27 , 30 , 31 , 34 , 35 ] are well documented. In sheep, Moghaddar et al [ 31 ] found a correlation close to 1 between GEBV computed from real versus imputed genotypes with an average imputation accuracy of 0.96.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the FImpute software (v 2.2) [11], as many studies have already pinpointed its good performance for imputation when compared to many other alternatives [16,35,43,44]. FImpute can use different sizes of rolling windows with a given overlap to scan the genomes of target and reference datasets.…”
Section: Genotype Imputationmentioning
confidence: 99%
“…We used the FImpute software (v 2.2) [11], as many studies have already pinpointed its good performance for imputation when compared to many other alternatives [16, 35, 43, 44]. FImpute can use different sizes of rolling windows with a given overlap to scan the genomes of target and reference datasets.…”
Section: Methodsmentioning
confidence: 99%